Tekst i paratekst: recepcija Witolda Gombrowicza u Hrvatskoj - Gverić Katana, Petra (Przekłady Literatur Słowiańskich, 2017)
Text and Paratext: The Reception of Witold Gombrowicz in Croatia From the year 2000 onwards, the number of works by Witold Gombrowicz translated into Croatian has decisively increased. The above is followed by a plethora of critical articles: features, commentaries, reviews, academic research articles, etc. The present article focuses on the issue of correspondence between the literary text and its paratext(s) in the target language culture, their potential interdependence, and their consequent impact on the reception of Gombrowicz’s work and the writer’s image. The analysis considers the factors contributing to Gombrowicz’s growing presence in Croatian cultural discourse. Keywords: Witold Gombrowicz, Croatian reception, paratext, translations, culture reception